Donor protection: Iron supplementation for frequent blood donors in Korea. (February 2020) - Lee, Seok Joon; Min, Hyuk Ki; Jang, Jin Sung; Lee, Sangwoon; Chung, Yousun; KIM, Moon Jung
Abstract: Objective: This study aimed to evaluate the effect of oral iron supplementation in frequent donors in Korea, based solely on donation history. Study design: The hemoglobin (Hb) level, ferritin level, soluble transferrin receptor (sTfR), total iron binding capacity (TIBC), and transferrin saturation of frequent donors at high risk for iron deficiency were compared to those of first donors. The frequent donors took iron supplements for 4 weeks and the same tests were repeated after 2 and 4 weeks to evaluate their effects. Result: A total of 53 male and 57 female frequent donors were recruited. After 4-week iron supplementation, among the men, the prevalence of a: low Hb level (<13.0 g/dL) decreased from 25% to 2%; low ferritin level (<15.0 ng/mL) decreased from 58% to 4%; iron deficient erythropoiesis (IDE) (log(sTfR/ferritin) ≥ 2.07) decreased from 77% to 33%. Among the women, the percentage of a: low Hb level (<12.0 g/dL) decreased from 44% to 9%; low ferritin level decreased from 79% to 11%; IDE decreased from 95% to 47%. In total, 15 male (28.3%) and 29 female (56.9%) blood donors reported undesirable side effects related to iron supplementation. No serious adverse events were reported. Conclusion: Ferritin level, a reliable indicator of iron status, increased and IDE decreased significantly after four-week iron supplementation in the female, but not in the male, donor group, compared to those of control donors. Four-week oral iron supplement was not enough to restore iron storage level in the male donor group.